Retrospective Analysis of Short-Term Respiratory Outcomes of Three Different Steroids Used in Clinical Practice in Intubated Preterm Infants - Nath, Sfurti; Reynolds, Anne Marie; Lakshminrusimha, Satyan; Ma, ChangXing; Hudak, Mark L.; Ryan, Rita M. (American Journal of Perinatology, 2019)
Objective This study aimed to compare short-term respiratory outcomes of three steroids (dexamethasone, hydrocortisone, and methylprednisolone) to facilitate extubation by improving respiratory status in preterm infants.Study Design This is a retrospective, single-center, cohort study of 98 intubated preterm infants ≤346/7 weeks' gestation, admitted to a 64-bed, level III neonatal intensive care unit at the Women & Children's Hospital of Buffalo, Buffalo, NY, between 2006 and 2012, who received a short course of low-dose steroids for lung disease after first week of life.Results Study infants received dexamethasone (34%), hydrocortisone (44%), or methylprednisolone (22%) based on clinical team preference. By day 7 after initiation of steroids, extubation occurred in 59, 44, and 41%, respectively, in infants on dexamethasone, hydrocortisone, and methylprednisolone (p = 0.3). The mean respiratory severity score (RSS = fraction of inspired oxygen × mean airway pressure), a quantitative measure of respiratory status, decreased by 44% for all infants and by 59% in the dexamethasone group by day 7.Conclusion Steroids improved short-term respiratory outcomes in all infants (RSS and extubation); by day 7, dexamethasone treatment was associated with the greatest decrease in RSS. Additional prospective, randomized trials of short-course low-dose steroids are warranted to substantiate these findings to guide clinical decision making and in evaluating differential steroid effects on long-term neurodevelopmental outcomes.
Keywords: bronchopulmonary dysplasia; postnatal steroids; preterm infants